2017
DOI: 10.1111/resp.13012
|View full text |Cite
|
Sign up to set email alerts
|

Global Strategy for the Diagnosis, Management and Prevention of Chronic Obstructive Lung Disease 2017 Report

Abstract: This Executive Summary of the Global Strategy for the Diagnosis, Management and Prevention of COPD, GlobalInitiative for Chronic Obstructive Lung Disease (GOLD) 2017 Report focuses primarily on the revised and novel parts of the document. The most significant changes include: (i) the assessment of chronic obstructive pulmonary disease has been refined to separate the spirometric assessment from symptom evaluation. ABCD groups are now proposed to be derived exclusively from patient symptoms and their history of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
732
1
55

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 634 publications
(796 citation statements)
references
References 348 publications
(581 reference statements)
8
732
1
55
Order By: Relevance
“…This indicates the importance of effective management of exacerbations and deterioration in patients affected by COPD. This finding is in-line with recent GOLD guidelines, that the best predictor of frequent exacerbations is a history of earlier treated events [1,25]. It is suggested that written negotiated action plans for worsening symptoms may lead to less respiratory-related hospitalization and all-cause hospitalizations as well as improved health status.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…This indicates the importance of effective management of exacerbations and deterioration in patients affected by COPD. This finding is in-line with recent GOLD guidelines, that the best predictor of frequent exacerbations is a history of earlier treated events [1,25]. It is suggested that written negotiated action plans for worsening symptoms may lead to less respiratory-related hospitalization and all-cause hospitalizations as well as improved health status.…”
Section: Discussionsupporting
confidence: 81%
“…Patients were included if they had not participated in the intervention at baseline. The independent variables are from baseline. Participation in patient education programParticipation in smoking cessation program UnivariableMultivariableUnivariableMultivariableIndependent variablesOR (95% CI) p OR (95% CI) p OR (95% CI) p OR (95% CI) p Constant 0.456 0.70Age, divided by 10 years1.04 (0.93, 1.17) 0.47 0.76 (0.62, 0.93) 0.0060.76 (0.62, 0.93) 0.006Gender (1 = man, 2 = woman)0.99 (0.80, 1.22) 0.89 1.37 (0.97, 1.95) 0.078 Social situation (0 = living alone; 1 = cohabiting)0.88 (0.67, 1.16) 0.37 0.79 (0.51, 1.23) 0.30 FEV 1 % of predicted value0.99 (0.99, 1.00) 0.045 1.00 (0.99, 1.01) 0.80 Exacerbations the last 12 months1.10 (1.02, 1.19) 0.0201.11 (1.02, 1.21) 0.0151.02 (0.89, 1.16) 0.79 Hospital admissions due to COPD the last 12 months1.14 (0.95, 1.35) 0.16 0.94 (0.65, 1.36) 0.73 Smoking, dichotomized0.69 (0.55, 0.87) 0.0020.69 (0.52, 0.85) 0.001  Dyspne_mMRC.01 1 Dyspne_mMRC.0 [1]1.34 (0.90, 2.01) 0.155 1.02 (0.47, 2.25) 0.95…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that home NIV may improve survival and the exacerbation rate [5,9], and for this reason this technique has also been mentioned as a potential treatment of chronic hypercapnic respiratory failure in the recent GOLD document [10]. Five further reviews will deal with this issue.…”
mentioning
confidence: 99%
“…The Global Initiative for Chronic Obstructive Lung Disease (GOLD) defines COPD as "a common, preventable and treatable disease that is characterized by persistent respiratory symptoms and airflow limitation that is due to airway and/or alveolar abnormalities usually caused by significant exposure to noxious particles or gases" (2). COPD can directly lead to or accelerate co-morbidities through hypoxia, dyspnea, polycythemia, pulmonary hypertension, and decreased activity ( Figure 1).…”
mentioning
confidence: 99%